Use of humanised rat basophilic leukaemia cell line RS-ATL8 for the assessment of allergenicity of Schistosoma mansoni proteins. - Wan, Daniel; Ludolf, Fernanda; Alanine, Daniel G.W.; Stretton, Owen; Ali Ali, Eman; Al-Barwary, Nafal; Wang, Xiaowei; Doenhoff, Michael J.; Mari, Adriano; Fitzsimmons, Colin M.; Dunne, David W.; Nakamura, Ryosuke; et al. (Public Library of Science, 2014)
BACKGROUND